PELATIHAN MEMBUAT SKENARIO DRAMA PADA KOMUNITAS YAYASAN ABAR INDONESIA - Gandadinata Thamrin; Richard Poeh; Heri Yulianto; Selvieana Indrawati; Merry Gading Mallibu (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Events held in schools and churches often use drama performances as entertainment or convey messages in the theme of the activity. This requires a story that can describe or provide a meaningful message to be conveyed to the audience present. But not everyone can make a good scenario and this is felt to be a necessity for the Abar Indonesia Foundation community where the community consists of teachers, lecturers, housewives, social workers, servants and Servants of God, as well as the general public who have a desire to learn. create a simple scenario that can be demonstrated at an event in the family, community, community, the August 17 event at the RT or RW, at school, at church or at a government office. From this need, the ABAR Indonesia Foundation asked Pelita Harapan University, Karawaci to provide an online training webinar "Training to create drama scenarios for the Indonesian Abar Foundation community". The purpose of this online webinar is at the request of the Foundation to be able to make good plans and develop the community's ability to create drama scenarios that can be used in community activities. The training on making simple drama scenarios with practical steps, planning and some important drama concepts was given during the webinar accompanied by short video examples and ended with a discussion and question and answer session. This activity was responded positively by the webinar participants and was supported by the LPPM of the Faculty of Economics and Business UPH and the UPH lecturer team as well as providing an output where participants gained additional basic knowledge of making scenarios, good storylines and useful for activities in the community.